2012
DOI: 10.1080/10426914.2011.577873
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Environmental Effects on Composite Repairs

Abstract: The scarf-joint technique is one of the latest techniques used for repairing composite aircraft structures. But this technique is mostly used at depot level repairing activities since it requires autoclave and other equipments. This article focuses on scarf joint comprised of vacuum and autoclave precured and co-cured composite patches bonded to autoclave and vacuum precured parent laminates. Autoclave and vacuum cured parent laminates and scarf joints were prepared and exposed to the same temperature and mois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…During service life of engineering structures, some initial damages, such as indentation, cracks, and breakage, are always inevitably formed due to environmental factors and external impacts [1]. Hence, the promptly and timely identification of initial damage is critical for structural integrity, mechanical performance retrieval and prolonging service life [2].…”
Section: Introductionmentioning
confidence: 99%
“…During service life of engineering structures, some initial damages, such as indentation, cracks, and breakage, are always inevitably formed due to environmental factors and external impacts [1]. Hence, the promptly and timely identification of initial damage is critical for structural integrity, mechanical performance retrieval and prolonging service life [2].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few investigations have been conducted on the moisture absorption properties of two-dimensional scarf joints and scarf-repaired laminates. Ahn et al [15] and Ealdi [16] performed tensile tests of composite scarf joints in hygrothermal environment conditions and found that the hygrothermal environments reduce tensile strengths of the joints. Feng et al [17] and scarf joints after moisture absorption.…”
Section: Introductionmentioning
confidence: 99%
“…And a scarf‐doubler repair method, bonding an external patch over the scarf patch and parent laminates, exhibited better resistance to elevated temperature than scarf repair. Elaldi examined the repair efficiency of the scarf joints under humidity and elevated temperature, which showed a dramatic reduction in the ultimate tensile strength after exposure to humidity and elevated temperature. And the hygrothermal failure modes were all adhesive failure.…”
Section: Introductionmentioning
confidence: 99%